Where rising powers meet: China and Russia at their North Asian border, 1900-2016 - Humphrey, Caroline (UK Data Service, 2019)
This data collection contains various data about current-economic and social practices in the border region shared between Russia, China and Mongolia, combining historical and anthropological methods of research. It contains informal interviews and pictures of representatives (informants) of the main focus groups, such as ethnic communities who straddle the border, such as the Nanai, Russians, and Mongols, border traders, and cultural activists among them. Interviews reflect their cross-border connections, including re-establishing of kinship ties, religious practices and social memory of separation and political upheavals between China and Russia, which greatly affected their everyday life at the border. Data reflects research findings to answer the question, how border society operates and how both countries manage their border economies, trade and migration. Along with detailed genealogies of some Buryat lineages, collection contains GIS maps of the Russian border region with China in Transbaikal region and fieldwork reports from various locations. Collection also includes data on research structure, workshops, publications, lectures and public talks of the Project members to share Project findings with a wider audience. The ‘Where Rising Powers Meet’ project aims to investigate what the Russian-Chinese border can reveal about the differing political economies of the two countries and their trajectories in the post-1991 era. Since each state exercises full sovereignty right up to their mutual border, there is no better place to compare the two remarkably dissimilar ways that economic development, the rule of law, citizen rights, migration, and inequality are managed. Yet state policies encounter volatile, more or less independent activities across this border. An important question the project will address is: how stable is this situation and what do the trends visible today indicate about the future of the two ‘rising powers’? This project, based at Cambridge but working in collaboration with colleagues in China, Russia, Mongolia, France and Denmark, is both multidisciplinary and multi-sited. The research team, composed of anthropologists, sociologists and economists, will be carrying out research at various sites along the border, from Mongolia in the west to Vladivostok in the east. The project has obtained the ethical approval of the University of Cambridge.